Venture capital funds: theoretical aspects - Jurevičienė, Daiva; Martinkutė, Aistė (Business: Theory and Practice, 2013)
The article deals with the form of corporate financing, which is becoming more popular yet is still underused, i.e. venture capital funds as well as their peculiarities and the procedure for attracting investments into a company. The paper summarises the main advantages and disadvantages of venture capital funds as well as their relation with national economic development. It analyses venture capital funds operating in Lithuania, investment strategies and dynamics. Additionally, it overviews the relation between the funds and the Government. According to the venture capital accessibility ratio, Lithuania is above the European Union average and overtakes such countries as Poland, Czech Republic and even Germany. However, the analysis of particular private capital transactions demonstrates that Lithuania could only compete with Central and Eastern European countries.SantraukaStraipsnyje  nagrinėjami  sparčiai  populiarėjantys,  bet  Lietuvoje  įmonėms  finansuoti  dar  retai  naudojami  rizikos  kapitalo fondai, jų ypatumai, investicijų pritraukimo ir investavimo į įmonę procesas. Apibūdinami pagrindiniai rizikos kapitalo fondų privalumai ir trūkumai, jų sąsaja su šalies ekonomikos plėtra. Nagrinėjami Lietuvoje veikiantys rizikos kapitalo fondai, jų investavimo strategija, atliktų investicijų dinamika, apžvelgiamas šalies vyriausybės sąryšis su šiais fondais. Pagal rizikos kapitalo prieinamumo rodiklį Lietuva viršija Europos Sąjungos vidurkį ir lenkia tokias šalis, kaip Lenkija, Čekija, net ir Vokietija. Tačiau, analizuojant konkrečius privataus kapitalo sandorius, Lietuva gali konkuruoti tik su Centrinės ir Rytų Europos šalimis.Rizikos kapitalo fondai: teoriniai aspektaiReikšminiai žodžiai: įmonių finansavimas, privatus kapitalas, rizikos kapitalo fondai, rizikos kapitalo fondų bruožai, įmonės investicinio patrauklumo vertinimas.